Study of a High Temperature–Resistant Shielding Material for the Shielding Doors of Nuclear Power Plants - Xiao-ling, LI; Rong-jun, Wu; Xiao-hui, Xu; Duo-fei, Zhang; Ming, YU (Frontiers in Energy Research, 2021)
An optimization design and application of a heat resistance shielding material are carried out according to the nuclear power plant source characteristics and special protection requirements such as LOCA. The composition of lead-boron polyethylene composite shielding material is optimized based on the genetic algorithm and Monte Carlo methods, then it is realized by blending modification and graft copolymerization to improve its high temperature resistant, shielding and mechanical properties. Then comprehensive properties such as mechanical, neutron shielding, damp heat aging, irradiation resistance and high temperature resistance experiments are tested. Those just prove the heat resistance lead-boron polyethylene composite shielding material has excellent performance; especially it is able to keep a complete structure in a high temperature environment up to 190℃ during 48 hours. Finally, the composite shielding material is applied to the shielding door design for reactor pit chamber. When the shield thickness is 60mm, the level of neutron dose rate is reduced by 10 times and that of γ dose rate is reduced by 5 times, which meet the requirements of radiation protection safety for nuclear power plant completely.